Alppihiihdon alkutaival : Pujottelu- ja tunturihiihto Suomessa 1920-luvulta 1960-luvulle - Kanerva, Jari (omakustanne, 2010)
The object of study in this thesis is Finnish skiing culture and Alpine skiing in particular from the point of view of ethnology. The objective is to clarify how, when, why and by what routes Alpine skiing found its way to Finland. What other phenomena did it bring forth? The objective is essentially linked to the diffusion of modern sports culture to Finland. The introduction of Alpine skiing to Finland took place at a time when skiing culture was changing: flat terrain skiing was abandoned in favour of cross-country skiing in the early decades of the 20th century, and new techniques and equipment made skiing a much more versatile sport. The time span of the study starts from the late 19th century and ends in the mid-20th century. The spatial focus is in Finland. People and communities formed through their actions are core elements in the study of sports and physical activity. Organizations tend to raise themselves into influential actors in the field of physical culture even if active individuals work in their background. Original archive documents and publications of sports organizations are central source material for this thesis, complemented by newspapers and sports magazines as well as photographs and films on early Alpine skiing in Finland. Ever since their beginning in the late 19th century skiing races in Finland had mostly taken place on flat terrain or sea ice. Skiing in broken cross-country terrain made its breakthrough in the 1920 s, at a time when modern skiing techniques were introduced in instruction manuals. In the late 1920 s the Finnish Women s Physical Education Association (SNLL) developed unconventional forms of pedagogical skiing instruction. They abandoned traditional Finnish flat terrain skiing and boldly looked for influences abroad, which caused friction between the leaders of the women s sports movement and the (male) leaders of the central skiing organization. SNLL was instrumental in launching winter tourism in Finnish Lapland in 1933. The Finnish Tourism Society, the State ...